Large‐Scale Nanoelectrode Arrays to Monitor the Dopaminergic Differentiation of Human Neural Stem Cells. (21st September 2015) - Kim, Tae‐Hyung; Yea, Cheol‐Heon; Chueng, Sy‐Tsong Dean; Yin, Perry To‐Tien; Conley, Brian; Dardir, Kholud; Pak, Yusin; Jung, Gun Young; Choi, Jeong‐Woo; Lee, Ki‐Bum
Abstract : A novel cell‐based biosensing platform is developed using a combination of sequential laser interference lithography and electrochemical deposition methods. This enables the sensitive discrimination of dopaminergic cells from other types of neural cells in a completely nondestructive manner. This platform and detection strategy may become an effective noninvasive in situ monitoring tool that can be used to determine stem cell fate for various regenerative applications.